PENGARUH MANAJEMEN PELAYANAN PUBLIK TERHADAP EFEKTIVITAS PELAYANAN PADA KECAMATAN LOA JANAN KABUPATEN KUTAI KARTANEGARA - Sudariono, Edi (PREDIKSI, 2012)
This study aimed to determine whether there is a positive effect of the Public Service Management Effectiveness Of Care In the District of Office Loa Janan Kutai regency.Purpose of the studies mentioned above, the analysis of the data used in this study is the Product Moment Correlation Coefficient (Pearson). The analysis showed a positive influence among the Effectiveness of Public Service Management Services at the District Office Loa Janan Kabupaten Kutai Kartanegara . It is based on the calculation of the states that count r is greater than r table is 0, 688; 0.312. For the critical value of n = 40 with a significance level = 0.05 thus the two variables have a positive relationship.After the count r is obtained, then the next writer to conduct testing using t-test. this hypothesis, the t value is greater than the value of t tables with significance level 0.05 for n - 2 = 38, ie 5.849; 1.686 or in other words that the influential Public Service Management.